Does celiac disease cause autoimmune sensorineural hearing loss? - Yazıcı, Alper; Yıldırım, Abdullah Emre; Konduk, Buğra Tolga (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The primary aim of this study is to identify whether an autoimmune sensorineural hearing loss is an extraintestinal neurological manifestation in adult CD patients. The secondary aim is to identify whether the duration of a gluten-free diet has an effect on the hearing levels of CD patients. Materials and Methods: This prospective study consisting of 103 adult CD patients and 79 healthy controls between May 2012 and August 2018 at the University of Gaziantep Gastroenterology and Otorhinolaryngology Departments. CD patients were divided into two groups as remission or active, according to their gluten-free diet duration and serum levels of anti-t-TG. The control group was checked both for CD symptoms and anti-t-TG serum levels. Both participants performed a pure tone audiometry after detailed ear nose and throat examination. Results: Only 4 of 103 CD patients showed sensorineural hearing loss. There was no statistically significant difference between hearing levels of the CD patients and the control group in both measurements of air and bone conductions. The hearing levels comparing the remission and active CD patients did not show any difference in air and bone conduction frequencies. Conclusion: In this study with a higher number of CD patients when compared with the previous studies, it has been shown that CD does not appear to cause autoimmune sensorineural hearing loss. In addition, the status of the patients regarding the activeness or the remission of CD did not display a differ between the CD patients in terms of hearing levels.